TOXIC - Vuja Syafrianti Alhidayah; Indrayuda Indrayuda (SENDRATASIK UNP, 2020)
The dance work "Toxic" aims to show that women's rights need to be respected in society because women are part of a social structure that needs to be properly managed and maintained so as not to be undermined by other social structures. The danceToxic is inspired by the phenomenon of social life of young people who have relationships with the opposite gender without following the norms that develop in society. This dance is made using the development of motives based on space, time, energy and developed using composition science. The form of presentation in this work is representational symbolic. "Toxic" is a dance work is inspired by changing patterns of the current life system of society from traditional societies bound by customary and religious rules transformed into a modern life that permeates the structure of the community itself, the culture that enters society today is acculturated and assimilate with existing culture. The dance "Toxic” is a dramatic dance in the form of a representational symbolic presentation that is manifested through motion, stage settings, make-up, fashion, lighting, and music.